2021
DOI: 10.7717/peerj.11263
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing fear during the pandemic: validation of the fear of COVID-19 scale in Polish

Abstract: Background The Fear of COVID-19 Scale (FCV-19S) is a brief self-report measure developed at the beginning of the coronavirus pandemic. The scale evaluates the emotional responses to COVID-19. To date, the FCV-19S has been translated and validated in about 20 languages and has been used in many published research. The current study aimed to validate the Polish version of the FCV-19S. Method The FCV-19S was translated into Polish using forward- and back-translation. From May 15th to June 15th 2020, a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 68 publications
9
33
1
1
Order By: Relevance
“…The FCV-19S is a psychometric tool created during the beginning of the SARS-COV2 pandemic to assess emotional response to the pandemic [ 15 ]. The FCV-19S may reflect depression, anxiety, stress, mental well-being, generalized anxiety disorder, psychological distress, post-traumatic disorder, and specific phobia [ 15 , 20 , 22 , 23 , 25 ]. The mean level of FCV-19S in our study patients was 18.9 ± 7.4 points (median 19 (13–24)).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The FCV-19S is a psychometric tool created during the beginning of the SARS-COV2 pandemic to assess emotional response to the pandemic [ 15 ]. The FCV-19S may reflect depression, anxiety, stress, mental well-being, generalized anxiety disorder, psychological distress, post-traumatic disorder, and specific phobia [ 15 , 20 , 22 , 23 , 25 ]. The mean level of FCV-19S in our study patients was 18.9 ± 7.4 points (median 19 (13–24)).…”
Section: Discussionmentioning
confidence: 99%
“…The mean level of FCV-19S in our study patients was 18.9 ± 7.4 points (median 19 (13–24)). Some studies on general populations in various countries found higher or lower fear of COVID-19, with mean FCV-19S from 13.2 to 27.3 points [ 15 , 20 , 22 , 23 , 24 , 25 ]. Comparison of the results is difficult due to the different times of assessment, different ages of the examined populations, and other varying characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations